Effect of three investing materials on tooth movement during flasking procedure for complete denture construction - Alaa’a M. Salloum (Saudi Dental Journal)
Problem statement: Tooth movement has been shown to occur during and after the processing of complete dentures. An understanding of this phenomenon may permit one to construct functional complete dentures that require less occlusal adjustment in the articulator and in the patient’s mouth. Purpose: The purpose of this study was to examine the effects of three different investing methods on tooth movement occurring during the processing of simulated maxillary complete dentures. Material and methods: Forty-five similar maxillary dentures were made using heat-polymerized acrylic resin, and assigned randomly to three experimental groups (n = 15 each) according to investing method: plaster–plaster–plaster (P–P–P), plaster–stone–stone (P-S-S), and plaster–mix (P–M). Specimens in all experimental groups were compression molded with denture base resin. Transverse interincisor (I–I) and intermolar (M–M) distances, and anteroposterior incisor–molar (LI–LM and RI–RM) distances, were measured with digital calipers at the wax denture stage (pre-polymerization) and after denture decasting (post-polymerization). Analysis of variance and Tukey’s test were used to compare the results. Results: M–M, LI–LM, and RI–RM movement was significantly greater in the P–P–P group than in the P–S–S and P–M groups; no significant difference in I–I movement was observed among groups. Transverse movement along M–M and I–I was significantly greater than anteroposterior movement in the P–P–P group; no significant difference among measurements was observed in the other two groups. Conclusion: The study results indicate that the use of dental stone or a 50:50 mixture of plaster and stone for investing of dentures is an important factor in efforts to control the magnitude of tooth movement. Keywords: Maxillary complete denture, Investing method, Plaster, Stone, Tooth movement